Development and Validation of a Clinical Guideline for Reproductive Health in Natural Disasters: A Mixed Methods Study - Ziba Raisi Dehkordi; Hadis Sourinejad; Elham Adibmoghaddam (Mashhad University of Medical Sciences, 2024)
Background & aim: Preparing to deal with natural disasters, is important for the health of the society, and a valid clinical guideline which fits the country's conditions can lead to a reduction in complications caused by the aforementioned disasters. Therefore, the present study was conducted to develop and validate the clinical guidelines for reproductive health in natural disasters.Methods: This mixed methods study was carried out in three phases. The first phase was a structured review of literature which systematically reviewed the articles and clinical guidelines related to the reproductive health in disasters. In the second phase, a qualitative study was conducted with the content analysis approach in order to identify the needs related to women's reproductive health in disasters, and a draft clinical guide was prepared. In the third phase, the validation of the prepared draft was carried out by a group of experts using the (RAND) Research and Development technique.Results: The themes obtained included the consequences of facing a disaster and the need to provide comprehensive services. The clinical guideline  consists of 5 chapters including an introduction on the importance of reproductive health in natural disasters, general clinical guidelines, prevention of physical and mental injuries in a crisis, access to reliable sources of information and the availability of the health services provider team. Conclusion: Correct management of crisis, empowering information skills and access to service providers in crises are of particular importance. Therefore, support of health care providers and training of service providers to learn about evidence-based performance in crises and their use is a necessary step to implement the clinical guidelines prepared in the country.